I wonder why Greeks built temples : and other questions about ancient Greece - Macdonald, Fiona (Danbury, Connecticut : Grolier Inc, 1999)
I Wonder Why Trees Have Leaves is jam-packed with fascinating facts about Ancient Greece, from 'Why did farmers beat their trees?' to 'Who ran the first marathon?'
Includes index
Keywords: History